Rice by-products – raw materials for alternative energy production in Ukraine - Marushchak, H.; Lisovyi, M.; Birina, N. (Problems of Environmental Biotechnology, 2019)
Assessment of bioenergy potential of rice varieties showed that by-products (straw and husk) of Vikont and Premium demonstrate the highest values of energy output; these varieties were studied to establish how the agronomic factors affect the formation of rice productivity with the final products meant for food and straw and husk being a source of bioenergy plant material as a solid biofuel. In field experiments the biggest yields of rice were obtained under applied mineral fertilizers N180P60K0 with seeding rate of 9 million of similar seeds per hectare for Vikont and Premium varieties at the levels of 9 and 8 t/ha, respectively. Thus, the optimal combination of rice farming techniques leads to high yields of the crop, and at the same time, to significant amounts of by-products suitable for further use. The results of the study showed that rice straw should be used as a source of alternative energy, ricegrowing regions of Ukraine could get heat energy equivalent to the amount released during combustion of 62 million m3 of gas. The economic effect of the transition from gas heat generators to the biomass heat generators leads to annual cost cutout of USD 192.3 thousand, and the payback period is 1.14 year. An additional source of alternative energy is the rice husk; the payback of launching a rice husk briquetting line is 1.6 year.